Clinical Features of Children with Diphtheria on Soetomo Hospital - Dwiyanti Puspitasari; Erna Supatmini; Dominicus Husada (Universitas Airlangga, 2012)
Introduction: Diphtheria is an important disease in children that could lead to fatal disease. East Java Province was declared to have Diphtheria outbreak in 2011 with increasing morbidity and mortality, including on Soetomo Hospital. Our paper aimed to describe the proﬁ le of diphtheria cases in children admitted at dr Sutomo Hospital.Method: This descriptive study reviewed all medical records of diphtheritic patients admitted to Dr. Soetomo Hospital, January 2004–December 2010, of concerns were clinical presentations, age, sex, immunizations status, complications, and outcomes.Result: From 148 diphtheria cases, 22.3% were bacteriologically proven; 53.4% were male with sex ratio 1.1:1. The age proportion of ≤ 5 years old, 5- ≤ 10 years old, and > 10 years old were 61.5%, 31.8%, and 6.7%. Fever occurred in 99% cases, sore throat, stridor and bullneck occurred respectively in 62.2%, 39.9%, and 29.7% cases. There were 56.8% severe and 41.9% moderate diphtheria. Subjects were immunized in 84%, but none of them have adequate immunization. Myocarditis, being one of the commonest complications occurred in 11.4% cases and tracheostomy was the second (4.0%). All of the death cases (7.9%) were unvaccinated and in severe form.Discussion: The mostly prevalent clinical manifestations in diphtheria children were fever and sore throat. Half of the cases came with severe diphtheria and most cases were inadequately vaccinated. Death occurred in the unvaccinated and severe form.